Policy making and implementation in agriculture: Tanzania's push for irrigated rice - Ole Therkildsen (Danish Institute for International Studies (DIIS), 2011)
Tanzania's 2005 push to increase rice production by ambitious rural investments in irrigation and by tariff protection of its rice industry from cheap imported subsidised rice has apparently highlevel political support. Yet, the implementation has run into problems: non-compliance with the tariff, substantial smuggling of cheap rice through Zanzibar, and low sustainability of irrigation schemes due to poor local-level operation and maintenance. These implementation problems arise because for the ruling elite, the political goals of winning elections and maintaining coalitions are more important than economic goals of strengthening the rice industry. Such political considerations influence how the enforcement capacity of tax authorities (to ensure tariff compliance and clamp-down on smuggling) and local governments (to ensure viable operation and maintenance of irrigation schemes) are actually used. Ideological notions about 'modernising agriculture' have also motivated the ruling elite to push for irrigation.
Keywords: 300; Agrarpolitik; Reisanbau; Bewässerung; Tansania